The Reinforcement of Zakat Management through Financial Technology Systems - M. Aulia Rachman; Annisa Nur Salam (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Financial technology or fintech, as the information media used to execute technology-based financial services, has become a great foundation in the effort toward enhancing the effectiveness and efficiency of financial services. The integrated zakat management system has been developed and needs innovations to be developed; several amil zakat institutions have utilized fintech as a more optimal services device in zakat management. This means that the fintech-based management of zakat will continue to grow and grow well, on both the market and consumer sides (especially for the aspect of demand), so it needs regulation, standardization and effort to guarantee the management of zakat using fintech media. This paper will offer concepts for the innovation, reinforcement, strategy, and legality regarding a technology-based management system for zakat, funded by the government or a relevant authority. Keywords: financial technology, Reinforcement, Management of Zakat